INFLUENCE THE FINANCIAL PERFORMANCE OF THE INITIAL RETURN AND COMPANY PERFORMANCE 2 YEARS AFTER IPO - Wahyunita, Wahyunita (Accounting, 2010)
The need for capital is the most important thing for the company. If the company can meet the needs of their funds from within the company, it can reduce the dependence from outside sources. However, if internal funds are not sufficient because the growth of the company, the management faced with the choice, that is debt or by issuing a exchange public. Go is one way in which the company to obtain additional funds in order to develop their business. One way that is often done by companies that will go public by selling shares of initial public offerings or often referred to as Initial Public Offering (IPO). Before the company is doing an IPO, usually the company issued a prospectus of a company that serves as a medium of communication between issuers and investors. This disclosed information will assist investors in making rational decisions about the risks and value of shares actually offered by issuers. Limitations information about the company can be a trigger of IPO underpricing. Information on companies that do an IPO is limited it difficult for investors to assess the level of benefits and risks that actual IPO shares. Of 17 samples of manufacturing firms that conduct an IPO on the Indonesia Stock Exchange during the period 2001 to 2005 can be inferred No financial variables that affect the initial returns, and there are changes in the company`s performance 2 years after the IPO, namely return on assets and profit margin. Meanwhile Current Debt to asset ratio and the ratio changed in the 2 years after the IPO even though the change is temporary and not consistence.